A revision of the Holarctic genus Larinioides Caporiacco, 1934 (Araneae: Araneidae) - Šestáková, Anna; Marusik, Yuri M.; Omelko, Mikhail M. (Zootaxa, 2014)
Аll known species of Larinioides Caporiacco, 1934 are revised. Seven species are recognised, of which one is transferred from Araneus Clerck, 1757 as a new combination, Larinioides jalimovi (Bakhvalov, 1981) comb. n. The first description of a male of L. jalimovi is given. The following four new synonyms are proposed: Epeira gracilis Menge, 1878 syn. n. and Aranea dumetorum islandicola Strand, 1906 syn. n. = L. patagiatus (Clerck, 1757); Araneus cungei Bakhvalov, 1974, syn. n. = Larinioides folium (Schrank, 1803); and Araneus sclopetarius Clerck, 1757 syn. n. = L. cornutus (Clerck, 1757). Detailed illustrations of habitus, copulatory organs, and identification keys of males and females of all Larinioides species are provided.